Psoriasis in children. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 2 - Joanna Narbutt; Adam Reich; Zygmunt Adamski; Grażyna Chodorowska; Andrzej Kaszuba; Dorota Krasowska; Aleksandra Lesiak; Joanna Maj; Agnieszka J. Osmola-Mańkowska; Agnieszka B. Owczarczyk-Saczonek; Witold Owczarek; Waldemar J. Placek; et al. (Termedia Publishing House, 2021)
Psoriasis is a chronic inflammatory skin disease which concerns approx. 1-3% population worldwide. In children psoriasis is less common, with the peak of morbidity in teenagers. Because of its more common prevelance in children in last decade, especially the disease with moderate and severe course, it is necessary to remind its clinical features and comorbidities. The aim of the recommendation of Polish Dermatological Society was to give the newest data on the psoriasis treatment in pediatric population which may be extremely important for everyday dermatological treatment. We described both topical and systemic treatments in details, including biological therapies.